2019
DOI: 10.1016/j.immuni.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory Aorta-Associated Macrophages Are Involved in Embryonic Development of Hematopoietic Stem Cells

Abstract: Summary Hematopoietic stem cells (HSCs) are generated from specialized endothelial cells of the embryonic aorta. Inflammatory factors are implicated in regulating mouse HSC development, but which cells in the aorta-gonad-mesonephros (AGM) microenvironment produce these factors is unknown. In the adult, macrophages play both pro- and anti-inflammatory roles. We sought to examine whether macrophages or other hematopoietic cells found in the embryo prior to HSC generation were involved in the AGM HSC-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 78 publications
6
92
0
Order By: Relevance
“…HCs in the aorta during the time of EHT are decreased/absent in the absence of Cx3cr1, and AGM HPC numbers and HSC in vivo repopulating activity are decreased in Cx3cr1 null embryos. 16 Similarly, we found that HPC numbers in the HBA of Cx3cr1 null embryos were significantly reduced. This is likely to be a consequence of decreased macrophage emigration to this region and is supported by the fact that macrophage (CD45 1 CD11b 1 F4/80 1 ) percentages were significantly (50%) reduced, and percentages of progenitor cells (cKit 1 CD41 low ) were also significantly reduced in the Cx3cr1 null HBA.…”
Section: Macrophages In the Embryonic Hba Regulate Hematopoiesis In Vivosupporting
confidence: 62%
See 3 more Smart Citations
“…HCs in the aorta during the time of EHT are decreased/absent in the absence of Cx3cr1, and AGM HPC numbers and HSC in vivo repopulating activity are decreased in Cx3cr1 null embryos. 16 Similarly, we found that HPC numbers in the HBA of Cx3cr1 null embryos were significantly reduced. This is likely to be a consequence of decreased macrophage emigration to this region and is supported by the fact that macrophage (CD45 1 CD11b 1 F4/80 1 ) percentages were significantly (50%) reduced, and percentages of progenitor cells (cKit 1 CD41 low ) were also significantly reduced in the Cx3cr1 null HBA.…”
Section: Macrophages In the Embryonic Hba Regulate Hematopoiesis In Vivosupporting
confidence: 62%
“…46 Single-cell RNA sequencing of highly enriched HS/PCs from mouse embryonic and fetal stages reveals some low Csf1r expression by these cells, 47 yet Csf1r cell tracing and other studies suggest that Csfr1 is not expressed by HSCs. 16,41 Thus, it is unclear in the HBA whether cells other than macrophages express Csf1r. Our analysis of sorted MacGreen HBA cells revealed that HPCs were distributed in the high-, intermediate-, and negative-expressing fractions (supplemental Figure 4A), and thus, has implications for the use of the in vivo Csf1r targeted DTA ablation model.…”
Section: Macrophages In the Embryonic Hba Regulate Hematopoiesis In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies suggested a link between the developing nervous system and enhancement of HSC emergence, as shown by the inductive effect of catecholamines in the mouse 85 and neuronal serotonin in the zebrafish 86 . Interestingly, from the yolk sac-derived wave, macrophages 87,88 and neutrophils 89 contribute with local sterile inflammatory signaling that promotes HSC emergence.…”
Section: Agm: the Cradle Of Hscsmentioning
confidence: 99%